A miniaturized, tethered, spectrally‐encoded confocal endomicroscopy capsule. Issue 5 (6th January 2019) - Kang, Dongkyun; Do, Dukho; Ryu, Jiheun; Grant, Catriona N.; Giddings, Sarah L.; Rosenberg, Mireille; Hesterberg, Paul E.; Yuan, Qian; Garber, John J.; Katz, Aubrey J.; Tearney, Guillermo J.
Abstract : Background and Objective: The tethered spectrally‐encoded confocal endomicroscopy (SECM) capsule is an imaging device that once swallowed by an unsedated patient can visualize cellular morphologic changes associated with gastrointestinal (GI) tract diseases in vivo . Recently, we demonstrated a tethered SECM capsule for counting esophageal eosinophils in patients with eosinophilic esophagitis (EoE) in vivo . Yet, the current tethered SECM capsule is far too long to be widely utilized for imaging pediatric patients, who constitute a major portion of the EoE patient population. In this paper, we present a new tethered SECM capsule that is 33% shorter, has an easier and repeatable fabrication process, and produces images with reduced speckle noise. Materials and Methods: The smaller SECM capsule utilized a miniature condenser to increase the fiber numerical aperture and reduce the capsule length. A custom 3D‐printed holder was developed to enable easy and repeatable device fabrication. A dual‐clad fiber (DCF) was used to reduce speckle noise. Results: The fabricated SECM capsule (length = 20 mm; diameter = 7 mm) had a similar size and shape to a pediatric dietary supplement pill. The new capsule achieved optical sectioning thickness of 13.2 μm with a small performance variation between devices of 1.7 μm. Confocal images of human esophagus obtained in vivo showed the capability of this new device to clearly resolve microstructural epithelial details with reduced speckle noise. Conclusions: We expect that the smaller size and better image performance of this new SECM capsule will greatly facilitate the clinical adoption of this technology in pediatric patients and will enable more accurate assessment of EoE‐suspected tissues. Lasers Surg. Med. 51:452–458, 2019. © 2019 Wiley Periodicals, Inc.